Identification and characterisation of seed storage protein transcripts from Lupinus angustifolius - Foley, Rhonda C; Gao, Ling-Ling; Spriggs, Andrew; Soo, Lena Y.C; Goggin, Danica E; Smith, Penelope M.C; Atkins, Craig A; Singh, Karam B (BMC plant biology, 2011)
Background In legumes, seed storage proteins are important for the developing seedling and are an important source of protein for humans and animals. Lupinus angustifolius (L.), also known as narrow-leaf lupin (NLL) is a grain legume crop that is gaining recognition as a potential human health food as the grain is high in protein and dietary fibre, gluten-free and low in fat and starch. Results Genes encoding the seed storage proteins of NLL were characterised by sequencing cDNA clones derived from developing seeds. Four families of seed storage proteins were identified and comprised three unique α, seven β, two γ and four δ conglutins. This study added eleven new expressed storage protein genes for the species. A comparison of the deduced amino acid sequences of NLL conglutins with those available for the storage proteins of Lupinus albus (L.), Pisum sativum (L.), Medicago truncatula (L.), Arachis hypogaea (L.) and Glycine max (L.) permitted the analysis of a phylogenetic relationships between proteins and demonstrated, in general, that the strongest conservation occurred within species. In the case of 7S globulin (β conglutins) and 2S sulphur-rich albumin (δ conglutins), the analysis suggests that gene duplication occurred after legume speciation. This contrasted with 11S globulin (α conglutin) and basic 7S (γ conglutin) sequences where some of these sequences appear to have diverged prior to speciation. The most abundant NLL conglutin family was beta (56%), followed by α (24%), δ (15%) and γ (6%) and the transcript levels of these genes increased 10(3) to 10(6) fold during seed development. We used the 16 NLL conglutin sequences identified here to determine that for individuals specifically allergic to lupin, all seven members of the β conglutin family were potential allergens. Conclusion This study has characterised 16 seed storage protein genes in NLL including 11 newly-identified members. It has helped lay the foundation for efforts to use molecular breeding approaches to improve lupins, for example by reducing allergens or increasing the expression of specific seed storage protein(s) with desirable nutritional properties.